Breastfeeding education in Chinese hospitals: A cross-sectional study. (September 2022) - Huang, Chuanya; Li, Linna; Zhang, Ting; Luo, Biru
Abstract: Background: Breastfeeding education plays a crucial role in improving breastfeeding outcomes and has been employed in many medical institutions across China. Objectives: To describe the current situation of breastfeeding education provided by hospitals to women in China, and to identify relevant factors associated with the exclusive breastfeeding rate at hospital discharge and the early breastfeeding initiation rate. Design: A cross-sectional study design. Settings and participants: We used an online survey platform called WenjuanXing to collect data from 2985 hospitals in China. Methods: We designed a questionnaire to collect data. The Mann–Whitney U test and Pearson's chi-square test were used to identify the differences between the different types and levels of hospitals. Binary logistic regression analysis was used to analyze the factors associated with the exclusive breastfeeding rate at hospital discharge and the early breastfeeding initiation rate. Results: A total of 2941 hospitals were included in the data analysis. In 86% of hospitals midwives were providing breastfeeding education on weekdays during the daytime. Information on how to deal with mastitis (80.8%) and weaning methods (71.5%) was less commonly provided to women. The hospitals often conducted breastfeeding education through antenatal education sessions and bedside health education, while 34.2% of hospitals used smartphone applications. The obstacles to conducting breastfeeding education in hospitals were a lack of full-time staff dedicated to breastfeeding education (43.3%) and limited funds invested in breastfeeding education (42.5%). A lack of full-time staff dedicated to breastfeeding education (OR, 0.689; 95% CI, 0.498–0.953) and a lack of space (OR, 0.697; 95% CI, 0.487–0.997) were associated with the exclusive breastfeeding rate at hospital discharge. Furthermore, a lack of full-time staff dedicated to breastfeeding education (OR, 0.372; 95% CI, 0.235–0.589) was associated with the early breastfeeding initiation rate. Conclusions: To improve breastfeeding outcomes, hospital managers and policymakers should increase the number of midwives and full-time staff who are dedicated to breastfeeding education, resolve the obstacles of limited funds and space for breastfeeding education, and explore more approaches to providing knowledge on breastfeeding to women and their families.